Memorials of the Irish West: John McHugh, Paul Durcan, and Harry Clifton - Kruczkowska , Joanna (Hungarian Journal of English and American Studies, 2020)
The article examines John McHugh’s sculpture (1950s Boat, 2009), Paul Durcan’s poem which it inspired “1950’s Boat (after John McHugh)” (2009)—both focusing on the Achill island—and another poem referring to the Blaskets, Harry Clifton’s “The Year of the Yellow Meal” (2012), trying to answer the question in what respect they stay close to realism and in what they approach experimentation. McHugh’s sculpture takes on an experimental form made of fragments of real stories, Durcan’s poem begins with this experimental sculpture and drifts towards realistic details but triggers experimental speculations, while Clifton’s poem mediates the Blasket biography through a style akin to magical realism in prose. All three palimpsestic works investigate issues of parochialism and marginalization faced with migration and cosmopolitanism, touch on the ethics (or rather, the lack) of gender policy and globalization, and by doing so, enquire about the Irish West’s disappearing culture.